Community Education Approach In Addressing Poverty As Determinant Of Stunting Prevalence In West Java: Multiple Linear Regression Analysis (Universitas Pendidikan Indonesia (UPI), 2025)
Stunting remains a critical public health challenge requiring comprehensive community education interventions in West Java Province. Despite national efforts, stunting prevalence remains above WHO standards, with significant variations across districts. Research gap exists in understanding how community education level influences stunting outcomes alongside poverty and healthcare access from a community education perspective. This study examines relationships between poverty-related factors and stunting prevalence across 27 West Java districts/cities. A cross-sectional design using 2023 secondary data from Central Bureau of Statistics and West Java Open Data was employed. Multiple linear regression analysis using JASP software examined poverty rate, average years of schooling (community education indicator), and healthcare facility access on stunting prevalence. Classical assumption tests including normality, homoscedasticity, and multicollinearity were performed. Results revealed significant positive correlation between poverty and stunting (r=0.628, p0.001). The regression model showed poverty rate (β=0.487, p=0.003), average years of schooling (β=-0.312, p=0.021), and healthcare access (β=-0.289, p=0.035) collectively explained 64.3% of variance in stunting prevalence (R²=0.643, F=13.25, p0.001). Average years of schooling demonstrated significant protective effect, indicating that enhanced community education level reduces stunting by 1.356% per additional schooling year. Findings emphasize community education's crucial role in stunting prevention, supporting integrated programs addressing health literacy, nutritional knowledge, and parenting education alongside poverty reduction. This study contributes to understanding how non-formal and community education interventions effectively address public health challenges in Indonesian contexts.